(3eNJUQ CaVd GdbQis - (3eMeO Hf YHO GdQMef GdUheZis; (3GdHhUjQj , TQa GdOjf CHh YHO Gddg eMeO Hf SYjO Hf MeGO Hf YHO Gddg GdUfgGLj GdeYQj,J (B696 (3g` s ((3Ydi Hf YHO Gddg Hf MehOI GdefUhQi s)
(3ChdgG (B:s
(3jbhd GdQGLi ef QHg GdYah hGdZaQGf eMeO Hf YHO GdQMef GdUheZi hHYO afXe GdEeGe CHdZ GdHdZGA GdUfgGLi fXeI GdgeRjI GdeSejGJ HCe GdbQi GdeTQhMI HTQM SeGg TGQMgG HCaVd GdbQi dCe GdbQi s
(3BNQgG (B:s
(3Ci GdehLhOGJ ai GdOfjG hGdBNQI hGdMeO ddg GdPi HQMeJg JJe GdUGdMGJ hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs